Unveiling in Vivo Subcutaneous Thermal Dynamics by Infrared Luminescent Nanothermometers - Ximendes, Erving Clayton
The recent development of core/shell engineering of rare earth doped luminescent nanoparticles has ushered a new era in fluorescence thermal biosensing, allowing for the performance of minimally invasive experiments, not only in living cells but also in more challenging small animal models. Here, the potential use of active-core/active-shell Nd3+ - and Yb3+-doped nanoparticles as subcutaneous thermal probes has been evaluated. These temperature nanoprobes operate in the infrared transparency window of biological tissues, enabling deep temperature sensing into animal bodies thanks to the temperature dependence of their emission spectra that leads to a ratiometric temperature readout. The ability of active-core/active-shell Nd3+- and Yb3+-doped nanoparticles for unveiling fundamental tissue properties in in vivo conditions was demonstrated by subcutaneous thermal relaxation monitoring through the injected core/shell nanoparticles. The reported results evidence the potential of infrared luminescence nanothermometry as a diagnosis tool at the small animal level.